Process-based modelling of isoprenoid emissions from evergreen leaves of Quercus ilex (L.) - Grote, R; Mayrhofer, S; Fischbach, R J; Steinbrecher, R; Staudt, M; Schnitzler, J.-P. (Atmospheric Environment, 2006)
Monoterpenes play an important role in regulating the trace gas composition of the lower troposphere. Therefore, realistic estimates of the daily as well as seasonal variations of monoterpene emission source strength on the Earth surface are required. Monoterpenes are emitted by Holm oak (Quercus ilex L.) and other species lacking speciﬁc foliar terpene storage structures and their development is dependent on light and temperature. In the present work we describe a process-based emission model taking into account the physiological/phenological state of Holm oak leaves and biochemical processes leading to the formation of monoterpenes. The model ‘seasonal isoprenoid synthase model–biochemical isoprenoid biosynthesis model’ (SIM–BIM2) is developed based on a previous version which was used to simulate isoprene emissions from deciduous oaks. The current model considers additional enzymatic reactions in Holm oak chloroplasts that lead to the formation of monoterpenes. The comparison of simulated and measured biochemical properties as well as emission rates displayed that the ability of the model to dynamically adjust monoterpene biosynthesis capacity by modulating the amount of monoterpene synthase activities in dependence of the weather pattern led to realistic simulations of light-dependent monoterpene emission rates. Differences to simulation results obtained by a widely used alternative model [Guenther, A.B., Zimmerman, P.R., Harley, P.C., Monson, R.K., Fall, R., 1993. Isoprene and monoterpene emission rate variability—model evaluations and sensitivity analyses. Journal of Geophysical Research 98, 12609–12617] are discussed.
Keywords: model development; monoterpene emission rates; monoterpene synthases; Quercus ilex; Seasonality; sim-bim2

Inventorying emissions from nature in Europe - Simpson, D; Winiwarter, W; Borjesson, G; Cinderby, S; Ferreiro, A; Guenther, A; Hewitt, C N; Janson, R; Khalil, M A K; Owen, S; Pierce, T E; Puxbaum, H; et al. (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 1999)
As part of the work of the Economic Commission for Europe of the United Nations Task Force on Emission Inventories, a new set of guidelines has been developed for assessing the emissions of sulphur, nitrogen oxides, NH,, CH,, and nonmethane volatile organic compounds (NMVOC) from biogenic and other natural sources in Europe. This paper gives the background to these guidelines, describes the sources, and gives our recommended methodologies for estimating emissions. We have assembled land use and other statistics from European or national compilations and present emission estimates for the various natural/biogenic source categories based on these. Total emissions from nature derived here amount to similar to 1.1 Tg S yr(-1), 6-8 Tg CH4 yr(-1), 70 Gg NH3 (as N) yr(-1), and 13 Tg NMVOC yr(-1). Estimates of biogenic NOx emissions cover a wide range, from 140 to 1500 Gg NOx (as N) yr(-1). In terms of relative contribution to total European emissions for different pollutants, then NMVOC from forests and vegetation are clearly the most important emissions source. Biogenic NOx emissions (although heavily influenced by nitrogen inputs from anthropogenic activities) are very important if the higher estimates are reliable. CH, from wetlands and sulphur from volcanoes are also significant emissions in the European budgets. On a global scale, European biogenic emissions are not significant, a consequence of the climate and size (7% of global land area) of Europe and of the destruction of natural ecosystems since prehistoric times. However, for assessing local budgets and for photochemical oxidant modeling, natural/biogenic emissions can play an important role. The most important contributor in this regard is undoubtedly forest VOC emissions, although this paper also indicates that NMVOC emissions from nonforested areas also need to be further evaluated. This paper was originally conceived as a contribution to the collection of papers arising as a result of the Workshop on Biogenic Hydrocarbons in the Atmospheric Boundary Layer, August 24-27, 1997. (Several papers arising from this workshop have been published in Journal of Geophysical Research, 103(D19) 1998.).
APS
Keywords: Emissions; land use; NOx; Volatile Organic Compounds

An overview of the Castelporziano experiments - Seufert, G; Bartzis, J; Bomboi, T; Ciccioli, P; Cieslik, S; Dlugi, R; Foster, P; Hewitt, C N; Kesselmeier, J; Kotzias, D; Lenz, R; Manes, F; et al. (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.
Keywords: air chemistry; Biogenic emission; ecophysiology; Mediterranean area; micrometeorology; Vegetation